Tinjauan Penolakan Pada Klaim Pasien BPJS Kesehatan di RSUD Tanjung Pura - Valentina; Mita Sari; Tri Widya Sandika (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
Rejection of claims is one of the obstacles in the BPJS Kesehatan claim collection process. The purpose of this study was to determine the description of administrative verification on the rejection of BPJS Kesehatan patient claims at Tanjung Pura Hospital. This type of research is descriptive qualitative. The population is all BPJS patient medical record files that were rejected in June 2021 counted 135 files and BPJS Kesehatan claiming officers at Tanjung Pura Hospital, totaling 2 people. The samples of this study were the medical record files of BPJS patients who were rejected in June 2021 and the BPJS claiming officers who were taken by saturated sampling. The instruments used are check list sheets and interview guidelines. Data was collected by using documentation, observation and interview methods. Data analysis was done descriptively. The results showed that there were 123 claim files (2.9%) which were rejected by BPJS Kesehatan from 4,253 claim files submitted. The reason for the rejection of the claim file was because all of them did not pass the verification of the service administration which consisted of the absence of a DPJP signature on the resume and proof of service, no referral letter attached, no inpatient indication/order sheet, and no indication of anesthesia attached to the operation report. This incompleteness is due to the lack of thorough examination of the completeness of the medical record file by the data analysis section and the absence of SOPs in the implementation of the claim process. It is recommended to the hospital director to make an SOP for claiming BPJS Kesehatan and to the claims officer and data analysis to be more thorough in checking the completeness of the BPJS Kesehatan claim file.